Digitalization and Branding of Agung Manunggal Village Owned Enterprises in the New Normal Era - Lestari, Ahdiana Yuni; Yuniarlin, Prihati; Misran, Misran; YH, Arya Ari Sepri (Jurnal Pengabdian Masyarakat Formosa, 2024)
This community service program aims to provide assistance in obtaining the legal entity status of BUMKal Agung Manunggal and provide assistance in the form of training and creation of the BUMKal Agung Manunggal Website. This program has five stages of implementation, Stage 1: Observation to identify problems and potentials that can be developed. Stage 2: Program conceptualization is the stage of developing the program to solve successful problems. Stage 3: Program Implementation, aims to carry out training and assistance related to the status of obtaining a legal entity as evidenced by the existence of a legal entity certificate and digital marketing training. Stage 4: Pre Test and Post Test. The results of this implementation show that after mentoring and managing the legal entity BUMKal Agung Manunggal has the status of a legal entity that has been issued by the Ministry of Law and Human Rights of the Republic of Indonesia through the Ministry of Villages of the Republic of Indonesia. Furthermore, the training program and the creation of the Agung Manunggal BUMKal website provide solutions to the limitations of BUMKal